Effect of Heat Compresses Hydrotherapy to Reduction of Pain Labor Stage 1st - Susiloningtyas, Luluk; Novitasari, Fransisika; Wulandari, Ratna Feti (STRADA : Jurnal Ilmiah Kesehatan, 2019)
Labor pain is an unpleasant stimulus that causes fear and worry. This situation will be stimulate an increase in catecholamineswhich can be cause interference with the strength of uterine contractions so that uterine insertion occurs if not corrected, which will be cause prolonged labor, so that’s necessary to prevent maternal care in the form of methods of pain transfer The One non-pharmacological method is heat compresshydrotherapy. The type of research was used Quasi Experimental withcross sectional approach one group pretest-posttest design. The results of data analysis stated that sig (p) = 0,000 where α = 0.05, p <α, means that therewas an effect of giving heat compress hydrotherapy to the reduction of labor pain in the active phase. Correlation or influence using Wilcoxon Correlation =-0.382.